A CASE OF CUTANEOUS TUBERCULOSIS UNDER STEROID & IMMUNOSUPPRESSANT THERAPY FOR DERMATOMYOSITIS - FUJITA, Masakuni; MIZUNO, Shiro; ARAKAWA, Kenichiro; DEMURA, Yoshiki; ISHIZAKI, Takeshi; SAWAI, Takahiro; WAKABAYASHI, Masanobu; AMESHIMA, Shingo; MIYAMORI, Isamu; TOTANI, Yoshitaka (Kekkaku, 2002)
A 44-year-old man had been admitted for high fever and leg edema on November 1998. By the laboratory data, electromyography, and muscle biopsy, he was diagnosed as having polymyositis. Steroid (prednisolone 60 mg/day) and immunosuppressant (methotrexate 7.5 mg/week) therapy was administered and the symptoms were improved, so he had been followed up in out-patient clinic. After half a year, high fever and leg edema relapsed and erythema on the bilateral forearms appeared, so he was admitted again on January 2000. The symptoms, skin involvement and laboratory data suggested the disease of dermatomyositis. Steroid pulse therapy was administered again. But the symptoms were not improved. Skin biopsy was performed but it showed only inflammatory changes. Several antibiotics and cyclospolyn A were undertaken but they were not effective. On February 12 th he passed away because of respiratory failure. The autopsy was undertaken and it revealed tuberculosis in the skin, subcutaneous tissues and muscles, however, pulmonary tuberculosis was not found. The patient with collagen disease is considered to be “compromised host”, especially during corticosteroid therapy. We must keep in mind potential incidence of tuberculosis and do careful clinical observation for early diagnosis and be prepared for antituberculous chemotherapy. Chemoprophylaxis for tuberculosis seems to be desirable for higher risk patients.